Bovine lactoferricin exerts antibacterial activity against four Gram-negative pathogenic bacteria by transforming its molecular structure - Pei, Jie; Xiong, Lin; Wu, Xiaoyun; Chu, Min; Bao, Pengjia; Ge, Qianyun; Guo, Xian (Frontiers in Cellular and Infection Microbiology, 2025)
The emergence and development of pathogenic bacterial resistance to antibiotics pose significant challenges to human health. Antimicrobial peptides (AMPs) are considered promising alternatives to conventional antibiotics. Lactoferricin (Lfcin), a cationic AMP located in the N-terminal region of lactoferrin, serves as the antimicrobial active center of the intact protein. The presence of two cysteines in Lfcin allows for the formation of an intramolecular disulfide bond, which may influence its molecular structure and antibacterial function. To investigate this hypothesis, we synthesized, purified, and identified bovine Lfcin along with two derivatives: Lfcin with a disulfide bond (Lfcin DB) and a mutated form that cannot form the disulfide bond (Lfcin C36G). We analyzed the circular dichroism spectra of these peptides under varying ionic and hydrophobic conditions, while their tertiary structures were predicted using AlphaFold3. Results indicated that increased ionic strength reduced the random coil ratios across all peptides. The secondary structure of Lfcin showed similar percentages with Lfcin C36G in the H2O and similar ratios with Lfcin DB under hydrophobic conditions. AlphaFold3-predicted models revealed two distinct structures: one predominantly adopting α-helix conformations and the other characterized by β-sheet topology. Furthermore, we evaluated the antibacterial activity of the peptides against four Gram-negative bacteria, including Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, and Salmonella gallinarum. The synthetic peptides demonstrated broad-spectrum antibacterial activity, with Lfcin exhibiting superior efficacy compared to its derivatives. Our findings suggest that Lfcin can reversibly interconvert between two distinct molecular states under varying ionic strengths and hydrophobic effects, with the resulting structural transformations enhancing its antibacterial function.